Gomisin N ameliorates lipopolysaccharide-induced depressive-like behaviors by attenuating inflammation in the hypothalamic paraventricular nucleus and central nucleus of the amygdala in mice - Ryota Araki; Yosuke Hiraki; Shoji Nishida; Yuka Inatomi; Takeshi Yabe (Elsevier, 2016)
Emotional impairments such as depressive symptoms often develop in patients with sustained and systemic immune activation. The objective of this study is to investigate the effect of gomisin N, a dibenzocyclooctadiene lignan isolated from the dried fruits of Schisandra chinensis (Turcz.) Baill., which exhibited inhibitory effects of the bacterial endotoxin lipopolysaccharide (LPS)-induced NO production in a screening assay, on inflammation-induced depressive symptoms. We examined the effects of gomisin N on inflammation induced by LPS in murine microglial BV-2 cells and on LPS-induced behavioral changes in mice. Gomisin N inhibited LPS-induced expression of mRNAs for inflammation-related genes (inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, interleukin (IL)-1β, IL-6 and tumor necrosis factor (TNF)-α) in BV-2 cells. Administration of gomisin N attenuated LPS-induced expression of mRNAs for inflammation-related genes, increases in the number of c-Fos immunopositive cells in the hypothalamus and amygdala, depressive-like behavior in the forced swim test and exploratory behavior deficits 24 h after LPS administration in mice. These results suggest that gomisin N might ameliorate LPS-induced depressive-like behaviors through inhibition of inflammatory responses and neural activation in the hypothalamus and amygdala.